ON KEY ISSUES OF IMPROVING TECHNICAL REGULATION IN THE FIELD OF FIRE SAFETY - Alevtina V. Novikova; Anna N. Varlamkina; Artur N. Katargin; Alexandr M. Solonenko (Актуальные вопросы пожарной безопасности)
The article considers the main issues of improving the provisions of the technical regulations of the Eurasian Economic Union «On requirements for fire safety and fire extinguishing equipment» (EAEU TR 043/2017), the development and implementation of interstate standards in development of the provisions of EAEU TR 043/2017. The problems of harmonization of requirements between regulatory documents in the field of construction and fire safety are studied. There is provided the information on the development of national standards and sets of rules in development of the provisions of Federal Law 123-FZ.